Pengaruh LKPD virtual laboratory dengan model kooperatif tipe SFE (student facilitator and explaining) terhadap kompetensi belajar fisika peserta didik di SMAN 12 Padang - wahyuni hafnisyah; masril masril; yenni darvina; hidayati hidayati (PILLAR OF PHYSICS EDUCATION, 2019)
The improvement of the competence of physics students can be done with the use of student worksheets and usage models that can support learning activities of students. This research aims to look at the influence of the LKPD virtual laboratory against the competence of physics students in SMA Negeri 12 Padang. The type of this research is Quasi Experiment Research and Posttest Only Control Group Design. The learning model applied in this research is a cooperative type SFE. Assessment on this research in the form of attitudes, knowledge, and skills. After doing research, and analyzing data obtained that there are influences which means the use of a LKPD virtual laboratory against the competence of learners. There is a growing attitude competency on each of his encounters with the experimental class attitude competency value higher than the control class. Competency in the knowledge, the average value of experimental class of 78,82 and average value of control class 74,38. Similarly, on the competency of skills with an average value of experimental class 79,72 and average value of control class 75,41. The results of the analysis of the correlation of product moment at 67,86% of knowledge competence and the competency of skills at 58,62%.  Keywords : LKPD, Virtual Laboratory, Competency, Cooperative